Comparison of the Accuracy of Fixture-Level Implant Impression Making with Different Splinting Techniques - Mehrdad Nateghi; Ramin Negahdari; Sahar Molaei; Ali Barzegar; Sepideh Bohlouli (International Journal of Dentistry)
Objectives. The impression-taking technique is one of the most critical factors that not only prevents the shrinkage caused by polymerization but also enhances the accuracy of implant impressions. Also, choosing the right time of taking impressions after splinting implants is one of the important criteria that affects the impression-taking technique. Accordingly, the present study aimed to evaluate the accuracy of different splint methods for implant impressions made at different times. Methods. In this in vitro study, a two-piece metallic index was prepared, and the patient’s jaw was simulated by placing self-cured acrylic resin in the lower part of the index. Then, two holes were made in the acrylic resin at a specific distance from each other, and the analogs were placed in these holes. Splinting of impression copings was carried out with autopolymerized acrylic resin (GC Pattern resin LS, GC America Inc., USA), and an open tray impression approach was performed. Thirty-six casts in three groups (n = 12) were fabricated from the acrylic model. After scanning the casts, the impression accuracy was compared between the three study groups by measuring the distance between the outer portions of the scan bodies screw-retained on implant analogs inside the cast using the Exocad software (2015.07 version). Group 1: splinting impression copings with autopolymerized acrylic resin and impression making immediately after the setting time (4 minutes); group 2: splinting and impression procedure after 17 minutes with splint sectioning and reconnection; group 3: splinting and impression procedure after 24 hours with splint sectioning and reconnection. The data were analyzed using SPSS 17 using the Kruskal–Wallis test. Results. The mean distance measured in group 1 was 19.14 ± 0.029 mm, which was significantly lower than the main model. The distances were 19.15 ± 0.039 and 19.159 ± 0.33 mm in groups 2 and 3, respectively. These two groups were not significantly different from the main model. Moreover, the mean distance measured in the three impression techniques was similar. Conclusions. There was no significant difference in the measurements between group 2, group 3, and the main model. Therefore, dentists can make an impression after 17 minutes to reduce chair time.